The Impact of E-Wallet Usage on Personal Financial Management: A Case Study of Generation Z - Selvi Permata Groda; Nugraha Kusbianto (Golden Ratio of Auditing Research, 2026)
This study examines the impact of e-wallet usage (EWU) on financial management (FM) among Generation Z in Indonesia, with a specific focus on the mediating role of financial literacy (FL). As digital natives, Gen Z exhibits high adaptability to financial technology (Fintech), particularly e-wallets, which offer convenience, speed, and integrated financial tools. However, the behavioral implications of e-wallet adoption—such as impulse buying and financial mismanagement—raise concerns about long-term financial well-being. Drawing on Financial Literacy Theory, the Behavioral Life-Cycle Hypothesis, and Self-Efficacy Theory, this research develops a conceptual framework linking e-wallet usage, financial literacy, and financial management. Using a quantitative approach, data were collected from 193 active Gen Z e-wallet users through a structured online survey. The study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to test four hypotheses. Results reveal that e-wallet usage significantly enhances both financial literacy and financial management. Moreover, financial literacy strongly influences financial management and mediates the relationship between e-wallet usage and PFM. These findings suggest that while e-wallets facilitate financial activities, their effectiveness in improving financial outcomes depends on users' financial literacy. Theoretically, this study extends digital finance literature by highlighting financial literacy as a behavioral pathway that translates technological engagement into responsible financial behavior. Practically, it offers policy recommendations for educators, fintech providers, and government stakeholders to promote digital financial literacy and responsible e-wallet usage among Gen Z. By fostering financial acumen alongside technological fluency, this research contributes to sustainable financial inclusion and resilience in the digital economy.